Endovascular Treatment Strategy for Direct Carotid-Cavernous Fistulas Resulting from Rupture of Intracavernous Carotid Aneurysms - Kobayashi, Nozomu; Miyachi, Shigeru; Negoro, Makoto; Suzuki, Osamu; Hattori, Koji; Kojima, Takao; Yoshida, Jun (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Reported treatments and outcomes in aneurysmal carotid-cavernous fistulas (CCFs) have been admixed with those of cases considered to be symptomatic of intracavernous aneurysm. However, aneurysmal CCFs have clinical features distinct from those of dural arteriovenous fistulas, and treatment strategies similar to those of traumatic CCF are required. We evaluated our experience in placing detachable balloons in the management of spontaneous CCFs due to rupture of an intracavernous aneurysm.METHODS: Six patients (one man, five women; mean age, 64.7 years) were treated for spontaneous direct CCF at our institution between 1995 and 2001. All patients presented with sudden ocular symptoms including exophthalmos, conjunctival injection, chemosis, and ocular motor palsies. Detachable latex balloons were used as the embolic material in five patients, and in one patient the cavernous sinus was packed transarterially with coils.RESULTS: All six patients were successfully treated by means of transarterial embolization, and symptoms improved within a week.CONCLUSION: Although other techniques using a transvenous approach and/or detachable coils may also be useful, embolization with detachable balloons should be a safe and effective method to immediately occlude the fistula.